Does Fertilizer N “Burn Up” Soil Organic Matter? - Grove, J. H. (2009)
This long-term Kentucky study evaluated the impact of tillage and N rates on crop yield and soil organic matter (SOM). After 29 years of continuous corn with a winter cereal cover crop, the combination of no-till cropping and fertilizer N use resulted in SOM levels similar to those in adjacent grass sod. There was no evidence that fertilizer N caused SOM loss.